Low‐level germline mosaicism of a novel SMARCA2 missense variant: Expanding the phenotypic spectrum and mode of genetic transmission - Nina Pan; Songchang Chen; Xiaoqiang Cai; Jianli Li; Tao Yu; He‐feng Huang; Jinglan Zhang; Chenming Xu (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Nicolaides–Baraitser syndrome (NCBRS) is a severe neurodevelopmental disorder with multiple abnormalities. To date, all pathogenic variants in SMARCA2 causing NCBRS are de novo and most are missense variants located in the ATPase domain of SMARCA2 protein. Methods In this study, a familial trio whole‐exome sequencing was performed on the proband presenting with intellectual disability, early‐onset epilepsy, and autistic features. A novel missense variant c.553C>G (p.Gln185Glu) in SMARCA2 was identified, which is located in the QLQ domain. The same variant was subsequently also found in the mother's ongoing pregnancy. Samples from accessible tissues such as saliva and sperm other than blood were collected from the parents, and the detection of the target variant was performed by amplicon‐based deep sequencing. Results Low‐level mosaicism of the target variant c.553C>G (p.Gln185Glu) was detected in the father's sperm with allele fraction of 2.8% by amplicon‐based deep sequencing, which was not detected in either parents’ blood or saliva specimens. Heterozygosity of this variant was confirmed in the proband. Conclusion This is the first report of paternal germline mosaicism for a SMARCA2 disease‐causing variant. In addition, the missense variant c.553C>G (p.Gln185Glu) in the QLQ domain causes mainly neurological and developmental phenotypes with unremarkable characteristic facial features and limb abnormalities. Our findings expand the phenotypic spectrum and mode of genetic transmission associated with the SMARCA2 variants.